2010
DOI: 10.1111/j.1529-8019.2010.01327.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recalcitrant Darier's disease with electron beam therapy

Abstract: Darier's disease (DD) is difficult to treat and has no cure. Although many modalities have been investigated, treatment options to date are largely unsatisfactory. Side-effect profiles have limited the use of many of these therapies, as has their ability to target only limited areas of disease. Furthermore, the effectiveness of most available treatments seems to be highly individualized, varying with disease severity and offering little alteration in the natural course of the disease. The present study reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…Two recent experiences described the efficacy of electron beam radiotherapy in Darier's disease [14, 15]. The first [14] used a dose of 2 Gy daily with energy of 7.5 MeV generated by a linear accelerator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent experiences described the efficacy of electron beam radiotherapy in Darier's disease [14, 15]. The first [14] used a dose of 2 Gy daily with energy of 7.5 MeV generated by a linear accelerator.…”
Section: Discussionmentioning
confidence: 99%
“…At the followup, the irradiated areas remained without recurrence, whereas new lesions in untreated body sites developed. The second study [15] reported a case of severe DD that was poorly responsive to known therapeutic modalities. This patient was treated with a total dose of 20 Gy in 10 fractions using 6 MeV electrons.…”
Section: Discussionmentioning
confidence: 99%
“…antibiotics (11), oral retinoid (acitretin or alitretinoin) (12)(13), ciclosporin (14)(15) and, more recently, lowdose naltrexone (16)(17)(18). Interventional treatments may also be performed, including (19): dermabrasion (20), wide excision (21), laser ablation (22)(23)(24), photodynamic therapy (25)(26)(27) and radiotherapy (28)(29).…”
Section: Introductionmentioning
confidence: 99%
“…Oral retinoids lead to improvement in approximately 90% of patients with severe disease (Engin et al, ). For recalcitrant localized disease, ablative techniques can be successful (Kittridge, Wahlgren, Fuhrer, Zirwas, & Patton, ; Lindelof, ). We present a patient with refractory DD with excellent response to three different modalities of radiation therapy: electron beam, intensity modulated radiation therapy (IMRT), and brachytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Oral retinoids lead to improvement in approximately 90% of patients with severe disease (Engin et al, 2015). For recalcitrant localized disease, ablative techniques can be successful (Kittridge, Wahlgren, Fuhrer, Zirwas, & Patton, 2010;Lindelof, 1987).…”
Section: Introductionmentioning
confidence: 99%